THE USE OF THE FLIPPED CLASSROOM TO ACTIVATE LEARNING IN STUDENTS OF FIRST LEVEL “D” OF SCIENCE AT MARIA AUXILIADORA SCHOOL IN ESMERALDAS - Ortiz Carrera, Aracelly Patricia (2019)
Tesis previa obtención del título de Licenciado/a en Lingüística Aplicada mención Inglés